The Effects of Corporate Governance Mechanisms and Audit Committee on Earnings Management of UK Retail Listed Companies - WANG, Xuefei (2020)
This study investigates the impacts of corporate governance mechanisms on the occurrence of earnings management activities among retail firms in the United Kingdom. In this research, the audit committee characteristics and board characteristics are taken into account and studied by a quantitative research method and secondary data. Regarding sample selection, 64 retail companies are chosen from London Stock Exchange (LSE) in recent four years. The modified Jones model (Dechow et al., 1995) is applied to estimate discretionary accrual, suggesting the significant importance of corporate governance practices in mitigating opportunistic managerial behaviour. First of all, board independence has a positive influence on constraining earnings management, suggesting outside directors are likely to discharge monitoring duties and discipline the management. Besides, the relation of board size with earnings management practices is negative, supporting that the large size of the board leads to inefficient monitoring of the board. In addition, a positive correlation among CEO duality on the occurrence of earnings management is proved, which means the dual role reduces the monitoring and control capability of the board. Moreover, audit committee independence is negatively associated with earnings management, thus suggesting external executives on the audit committee exercise more effective oversight to ensure the transparency in financial statements. In contrast, there is no relationship between audit committee size and the occurrence of earnings management. This paper provides valuable insights for regulators to implement corporate governance practices, highlight the important role of corporate governance mechanisms among retail listed firms in the United Kingdom.